Smartphones and Digital Tablets: Emerging Tools for Fisheries Professionals. Issue 10 (18th October 2013) - Gutowsky, Lee F. G.; Gobin, Jenilee; Burnett, Nicholas J.; Chapman, Jacqueline M.; Stoot, Lauren J.; Bliss, Shireen
ABSTRACT: Smartphones and digital tablets are used to collect data for agricultural, geographical, and medical research. Science professionals find these devices attractive because they contain many useful hardware accessories (e.g., camera, Global Positioning System [GPS], accelerometer) and the capacity to access and customize software applications (apps). To enhance student learning, some educators are also integrating tablets into curricula for both indoor and outdoor course work. Recently, fisheries professionals have begun using these devices for data collection and public outreach and awareness. With new waterproofing technology, cases, and peripheral adapters, smartphones and digital tablets are continually becoming more relevant for data collection and education in fisheries. Here, we synthesize some of the available information on smartphone and tablet use for data collection and education and explore some current uses and future opportunities for these devices in fisheries. Overall, our objective is to demonstrate that smartphones and digital tablets are useful tools for fisheries professionals, including technicians, managers, and educators.